The discovery and development of HIV therapy: the new challenges - Carlo Federico Perno (Istituto Superiore di Sanità, 2011)
The therapy of HIV infection has been dramatically improved over the years, and allowed the achievement of unexpected results. The availability of many drugs, and the knowledge of HIV related pathogenesis, helped in selecting highly effective antiviral therapies, yet today a major challenge stands, that is the selection of the best regimen(s) in clinical practice. In this frame, evidence-based medicine remains a cornerstone of modern medicine, but its structure needs to be adapted to the new challenges, made by an excess of information (not always fully reliable), by highly sophisticated statistical systems that may overlook the clinical practice despite their ability to define the statistical significance, and the limited number of independent controlled studies. The revision of the criteria of evidence-based medicine, and their adaptation to the new tools available, may allow a better contribution to the definition of the best therapy for each single patient.